Localization of the Priming Factors CAPS1 and CAPS2 in Mouse Sensory Neurons Is Determined by Their N-Termini - Staudt, Angelina; Ratai, Olga; Bouzouina, Aicha; Fecher-Trost, Claudia; Shaaban, Ahmed; Bzeih, Hawraa; Horn, Alexander; Shaib, Ali H.; Klose, Margarete; Flockerzi, Veit; Lauterbach, Marcel A.; Rettig, Jens; et al. (Frontiers in Molecular Neuroscience, 2022)
Both paralogs of the calcium-dependent activator protein for secretion (CAPS) are required for exocytosis of synaptic vesicles (SVs) and large dense core vesicles (LDCVs). Despite approximately 80% sequence identity, CAPS1 and CAPS2 have distinct functions in promoting exocytosis of SVs and LDCVs in dorsal root ganglion (DRG) neurons. However, the molecular mechanisms underlying these differences remain enigmatic. In this study, we applied high- and super-resolution imaging techniques to systematically assess the subcellular localization of CAPS paralogs in DRG neurons deficient in both CAPS1 and CAPS2. CAPS1 was found to be more enriched at the synapses. Using – in-depth sequence analysis, we identified a unique CAPS1 N-terminal sequence, which we introduced into CAPS2. This CAPS1/2 chimera reproduced the pre-synaptic localization of CAPS1 and partially rescued synaptic transmission in neurons devoid of CAPS1 and CAPS2. Using immunoprecipitation combined with mass spectrometry, we identified CAPS1-specific interaction partners that could be responsible for its pre-synaptic enrichment. Taken together, these data suggest an important role of the CAPS1-N terminus in the localization of the protein at pre-synapses.